Risk factors for carpal tunnel syndrome in pregnant women - Lia Dwi Prafitri; Wahyu Ersila; Dzikra Nurseptiani (Faculty of Medicine, Universitas Islam Indonesia, 2022)
Background: Carpal Tunnel Syndrome (CTS) affects 267 people out of every 100,000 in the United States each year, with a prevalence of 9.2% in women and 6% in men. Women are three times as vulnerable as men. Pregnancy can be a risk factor for CTS, which typically occurs in the first and third trimesters and is bilateral. Signs and symptoms will be persistent if CTS develops in early pregnancy and may recur in subsequent pregnancies. Hormonal changes during pregnancy can put you at a greater risk of developing CTS symptoms because the structure of the wrist enlarges and can put pressure on the nerves in the wristObjective: This research aims to identify risk factors for the occurrence of CTS in pregnant women. Early detection of risk factors for CTS needs to be done early in pregnancy to be able to make appropriate prevention and treatment efforts for pregnant women who experience CTS.Methods: TThis research employed an observational method in conjunction with quantitative analytical research. The population of this research included all pregnant women in the working area of Kedungwuni Health Center I and II in Pekalongan Regency. The sampling technique used was cluster random sampling, with 108 pregnant women meeting the inclusion criteria. Data collection methods entailed interviews and documentation using questionnaires, Phalen's test sheets, and nutritionalstatus measuring tools such as the microtome and bathroom scale. The risk factors to be studied are the relationship between employment status, parity, the incidence of CED, nutritional status before pregnancy, and a history of the disease, with the incidence of CTS. Chi-Square and Odds Ratio was used in bivariate analysis, while multivariate analysis used logistic regression.scar. Significance was set at p<0.05.Results: The incidence of CTS is significantly related to employment status, nutritional status before pregnancy, CED incidence, parity, and previous medical history (p-value < 0.05).Conclusion: Starting from the strongest, the strength of the relationship shown by the OR results is employment status (OR 7,231), medical history (OR 6,214), and the incidence of CED (OR 3,428). Occupational status has the highest odds ratio, making it the most important factor in the occurrence of CTS in pregnant women in the Pekalongan Regency